Study of the full-service and low-cost carriers network configuration - Oriol Lordan (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The network strategies used by airline carriers have been a recurring subject in air transport research. The aim of this paper is to investigate the relationship between the different operational characteristics of the airline and its route network configuration. Design/methodology/approach: The two main airline carrier typologies - Full-Service and Low-Cost carriers - are analysed using empirical models developed on complex network research relating them to the business model of the airlines. Findings and Originality/value: Just in Europe, one can differentiate between Full-Service and Low-Cost Carriers by complex network analyses. In this process, it has been also found that new concept Low-Cost Carriers, such as Vueling, have network properties closer to Full-Service Carriers. Research limitations/implications: This paper has a limited sample, as includes 26 airline case studies from Europe, United States and Asia. Practical implications: The analysis carried out in this research can help to the assessment of the evolution of the strategies of airline carriers, and has also operational implications, since the configuration of an airline route network can determine its resilience to attacks and errors. -Social implications: A better understanding of the properties of airline route networks can benefit airlines, passengers and another stakeholders of the air transport industry. Originality/value: Current research on air transport networks has only considered the global or regional level, but few studies have addressed the study of airline transport networks, and its relationship with their business model.
Keywords: 650; complex networks; airline strategy; Full-Service Carriers; Low-Cost Carriers